Особливості обліку операцій в іноземній валюті та банківських металах на умовах спот - Ружанська, Т.В. (Культура народов Причерноморья, 2013)
У статті розглядаються методичні та організаційні підходи до бухгалтерського обліку
операцій в іноземній валюті та банківських металах на умовах спот. Проаналізований чинний порядок
відображення в бухгалтерському обліку операцій з купівлі іноземної валюти та банківських металів за
національну валюту за умовами спот та запропонований новий порядок відображення в
бухгалтерському обліку операцій в іноземній валюті та банківських металах на умовах спот, який
передбачає використання позабалансових рахунків. В статье рассматриваются методические и организационные подходы к бухгалтерскому
учету операций в иностранной валюте и банковских металлах на условиях спот. Проанализирован
действующий порядок отображения в бухгалтерском учете операций покупки в иностранной валюте и
банковских металлах за национальную валюту на условиях спот и предложен новый порядок
отбражений в бухгалтерском учете операций в иностранной валюте и банковских металлах на
условиях спот: который предусматривает использование внебалансовых счетов. The article deals with methodological and organizational approaches to accounting transactions in
foreign currencies and precious metals on spot conditions. Analyze the effect of the display order of the
accounting transactions of purchase of foreign currency and precious metals in the national currency on spot
conditions and proposed a new procedure otbrazheny in accounting transactions in foreign currencies and
precious metals on spot conditions: which involves the use of off-balance sheet accounts.
Because, despite the risks inherent in market transactions "spot, such agreements are available that provide a
large number of participants, and relatively simple foreign exchange transactions. In addition, today crucial in
choosing agreements are predominant demand is for immediate operation, making it possible in the short term
to exchange a certain amount of currency and get the equivalent.
In the foreign exchange market transactions "spot" is the most common and account for the vast majority of
foreign exchange transactions.
Currently accounting transactions in foreign currencies and precious metals on a spot is on the balance sheet.
The paper proposes to make records of transactions in foreign currencies and precious metals on a spot with the
use of off-balance sheet accounts .